Type D personality and metabolic syndrome among Finnish female municipal workers - Susa Majaluoma; Tellervo Seppälä; Hannu Kautiainen; Päivi Korhonen (BMC, 2025)
BackgroundType D personality is a combination of high negative affectivity (NA) and high social inhibition (SI). This personality trait is suspected to impair cardiovascular patients' recovery. The 2016 European Guidelines on cardiovascular disease prevention in clinical practice recommend screening of psychosocial risk factors as Type D personality. The aim of this study was to assess the relationship between Type D personality and Metabolic syndrome (MetS) in working-age female population.
MethodsSix hundred thirty-four female employees with mean age of 4810years were evaluated. Type D personality and its components (NA) and (SI) were screened with DS14 questionnaire. The definition of MetS was based on measurements done by trained medical staff. We investigated the relationship between Mets and Type D personality, NA and SI using the logistic regression models adjusting for age, education years, leisure-time physical activity, smoking, alcohol use and depressive symptoms.
ResultsThe prevalence of Type D personality was 10.6% (n=67) [95% CI: 8.3 to 13.2] and MetS 34.7% (n=220). Type D personality or its subcomponents were not associated with MetS. Women with Type D personality had significantly worse quality of sleep and lower LTPA. They were also more often unsatisfied with their economic situation, they had more often depressive symptoms and psychiatric disorders than non-D type persons. There were no differences in risk factors for cardiovascular diseases.
Conclusion Screening for Type D personality among working- age, reasonably healthy female population seems not to be practical method for finding persons with risk for cardiovascular disease.